2008
DOI: 10.1103/physreve.78.056403
|View full text |Cite
|
Sign up to set email alerts
|

Generation of intense proton beams from plastic targets irradiated by an ultraintense laser pulse

Abstract: Proton beams generated from thin aluminum and Mylar foil targets that are irradiated by a 30fs Ti:sapphire laser pulse with an intensity of 2.2x10;{18}Wcm;{2} were investigated. Protons from the Mylar targets were observed to have an energy higher by a factor of 2 and were higher in number by an order of magnitude as compared with those generated from the aluminum targets. The maximum proton energy of 1.3+/-0.12MeV obtained from the Mylar target was found to be similar with previous observations that used lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…First of all, plastic targets generate more protons by orders of magnitude with higher energy by a few factors, which have been already observed in several experiments. [37][38][39] In both materials, the maximum proton energy increases as the duration of the ASE pulse decreases. However, in the case of aluminum targets, the highest maximum energy increases as target thickness decreases, while no such dependence can be found for Mylar ® targets.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…First of all, plastic targets generate more protons by orders of magnitude with higher energy by a few factors, which have been already observed in several experiments. [37][38][39] In both materials, the maximum proton energy increases as the duration of the ASE pulse decreases. However, in the case of aluminum targets, the highest maximum energy increases as target thickness decreases, while no such dependence can be found for Mylar ® targets.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that more intense proton beams from the plastic target than those from a metal target can be explained by the ARIE model in the intensity range of 10 17 -10 19 W / cm 2 . 37 In this model, the maximum proton energy is written as the following:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of an intense laser beam with an underdense plasma can lead to rapid heating of the electrons and acceleration of ions [8,9]. In target normal sheath acceleration (TNSA) [10][11][12][13][14][15][16][17][18][19], a minority species of light ions (typically protons) is accelerated by the hot sheath of laser-heated electrons normal to a solid target. The TNSA scheme has successfully been used to accelerate protons to several tens of MeV, usually with a wide spectrum of energies [18].…”
Section: Introductionmentioning
confidence: 99%
“…The target normal sheath acceleration (TNSA) model 4 or the isothermal expansion model 5 is known to effectively describe the proton beam from metal foils. 7 Acceleration by a resistively induced electric field (ARIE) 8,9 has been proposed to account for the phenomena occurring in plastic foils.…”
Section: Introductionmentioning
confidence: 99%